The Perception of Islamic Studies Learners Towards a New Approach in Knowledge Transfer for Islamic Studies Programmes at OUM - Hamidah Mat; Wan Mohd Al Faizee Wan Ab Rahaman; Wan Mohammad Ubaidillah bin Wan Abas; Khairul Hamimah Mohd Jodi; Cik Norazlina Mohamad (2021)
Knowledge transfer is the sharing or dissemination of knowledge and the provision of input for problem solving. The Covid-19 pandemic has changed lives in various ways, including the way of learning and transferring knowledge. The process of knowledge transfer has also changed due to technologyassisted learning and the needs of the process. According to Islamic scholars, the authenticity of knowledge is confirmed through a specific medium, i.e., face-to-face meeting or discussion with a teacher (talaqqi). Thus, some may not be open to a new approach in knowledge transfer in the field of Islamic studies, which is online learning. This study is aimed at identifying the perception of Islamic Studies students at OUM towards the medium of knowledge transfer in Islamic Studies programmes. The quantitative method of questionnaires was used to obtain data. The findings of the data, which was analysed using descriptive statistics on SPSS, revealed that the perception of a sample of Islamic Studies students at OUM towards the concept of online learning was aligned with the proposed transfer of knowledge based on the Islamic view. They presented a high level of understanding, acceptance, and recognition of the benefits and usefulness of the medium of knowledge transfer in Islamic Studies.